Approbation of the mechanism of economic reliability on the example of an industrial enterprise - A. R. Terentyeva (Омский научный вестник: Серия "Общество. История. Современность")
The article considers the operation of the cascade model of the mechanism of economic reliability based on the process-technological approach. To analyze the current state of an industrial enterprise, a generalized indicator of the level of economic reliability in dynamics over six years has been established using the desirability function. Absolute indicators for the main processes of an industrial enterprise have been translated into dimensionless ones, and partial indicators of desirability have been found. Comparing the level of economic reliability with the estimates of the Harrington desirability scale meets the requirements of finding a generalized economic reliability function with a set of criteria indicators. An analysis of the potential level of economic reliability was also carried out and compared with the actual level of economic reliability. The analysis of the level of organization of ensuring economic reliability by organizational-managerial and productiontechnological modules revealed the bottlenecks of an industrial enterprise. The purpose of the work is to test the mechanism of economic reliability on the example of an industrial enterprise. The result of the developed methodology is the formation of a mechanism of economic reliability based on the processtechnological approach and the introduction of this mechanism into the economic activity of an industrial enterprise. The results obtained can be applied at industrial enterprises of any scale of production and organizational and legal form in the conditions of modern technological dynamics to increase the level of economic reliability. The author of the article came to the following conclusions: the implemented mechanism of economic reliability in the activity of an industrial enterprise allows identifying bottlenecks, as well as developing measures to eliminate them, thereby increasing the level of economic reliability; the action of this mechanism should be continuous, since the intensification of technological dynamics is an aggressive factor influencing the efficiency, stability and sustainability of the functioning of an industrial enterprise. The methodological basis of the study was made up of general scientific methods of classification, generalization, comparison, analysis.